Child Labour in Thamel's Hospitality Industry: A Study on Causes and Effects (Pragyaratna प्रज्ञारत्न, 2023)
The main objective of the study was to draw out the economic condition of the family along with the causes of child labour and its impact on health education. The purposing sampling method was taken to select the respondent.135 respondents were selected by convenient sampling methods. The low educational status of child labour was the major problem. The health condition of the labour was weak due to unhealthy working environment. Out of 135 respondents, 40 (29.62%) respondents were suffering from different kinds of disease. The respondents were found to be lacking of proper educational status. All of them were found to have studied below SEE level. Children's work is very harmful, hazardous, or is in other ways exploitative can create, exacerbate, or perpetuate an intergenerational cycle of poverty, malnutrition and social disadvantage.